The wellbeing paradox in Hungarian local sustainable agriculture: a health psychology approach - Ilona Liliána Birtalan; Imre Fertő; Ágnes Neulinger; József Rácz; Attila Oláh (BMC, 2022)
Abstract Background The literature suggests that farmers' work involves a number of operational difficulties. Although alternative food networks address the majority of their problems, they can potentially generate new hardships. The aim of this study is to examine the situational and engagement-related work difficulties associated with the everyday world of Community Supported Agriculture (CSA) farmers. Methods This study used the health psychology approach, namely interpretive phenomenology, to understand the social determinants of farmers' working lives in CSA and to explore mental health challenges within the practices of local sustainable farming. To collect data, semi-structured, in-person interviews were conducted with CSA farmers in Hungary. Results Our study shows that new modes of consumer-producer connectivity create novel situations and issues which farmers are forced to address. Three personal experiential themes emerge from the data to describe CSA farmers' work difficulties: (1) Conflicted autonomy; (2) The pressure of boxes; (3) Social overload. The difficulties for CSA farmers seem to be rooted in the economic characteristics of alternative agriculture where farmers organize food production for the satisfaction of consumer needs. In addition, structural conditions require several different CSA farmer roles, which could even be conflicting. Conclusion This study provides participants' perspectives on the health and wellbeing costs of sustainable farming. Newer producer-consumer connections require both time and experience and involve extra effort or skills, but farmers often lack these abilities. The results show how perceptions of work processes relate to the general framework of CSA, which necessitates a distinct strategy for farm management.